Chapter 6: Levan Polysaccharide for Biomedical Applications - (:unkn) unknown (Royal Society of Chemistry, 2021)
Levan is a homopolysaccharide of fructose units containing β-2,6 linkages between the fructosyl moieties on its backbone with occasional β-2,1 branches, and it is synthesized by a diverse genera of both Gram-positive and Gram-negative bacteria, fungi, some flowering plants, and some halophilic Archaea. With the discovery of its unique physiochemical features such as exceptionally low intrinsic viscosity and high adhesive strength, and bioactive characteristics as an anti-oxidant, anti-carcinogenic, prebiotic, hypoglycemic, and cell-proliferating agent, growing attention toward this polysaccharide has been seen especially in recent years. As a result, levan and its chemically modified derivatives have been the subject of several biomedical applications via development of novel levan-based biomaterials like films, electrospun and 3D-printed scaffolds, and hydrogels. This chapter summarizes the most recent findings from studies that focus on biomedical aspects of levan polysaccharide. © The Royal Society of Chemistry 2021.